PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING BERBANTUAN GEOGEBRA MATERI BANGUN RUANG SISI DATAR - Indah Feliya Santika; Nur Izzati; Nur Asma Riani Siregar (Universitas Batanghari Jambi, 2026)
This study aimed to create digital teaching materials that help students understand abstract geometric ideas and promote active engagement in mathematics learning. The objective was to develop an electronic student worksheet (E-LKPD) using the problem-based learning (PBL) model and supported by Geogebra, for eighth-grade students studying three-dimensional geometry topics. The research employed the Research and Development (R&D) 4D model by Thiagarajan, encompassing the Define, Design, Development, and Disseminate stages. Data were collected through questionnaires and tests, including expert validation sheets, student response questionnaires, and learning outcome tests. The data were analysed using both qualitative and quantitative techniques. The results indicated that the developed E-LKPD met validity criteria, with average material validity of 89.13%, language validity of 80.66%, and media validity of 87.89%. The practicality level achieved an average score of 81.97%, indicating a highly practical level. revealed that the use of the E-LKPD significantly improved students learning outcomes and increased their participation These findings suggest that the PBL-based E-LKPD supported by Geogebra is suitable for use as an innovative teaching material to enhance meaningful mathematics learning.